Programmable Logic Controllers (5th Edition) - Bolton, William (Elsevier, 2009)
This easy-to-read book continues to be a straight-forward text that presents the principles of PLCs, while not tying itself to one vendor or another. Extensive examples and chapter ending problems utilize several popular PLCs currently on the market, highlighting understanding of fundamentals that can be used no matter the specific technology. Ladder programming is highlighted throughout with detailed coverage of design characteristics, development of functional blocks, instruction lists, and structured text. Methods for fault diagnosis, testing and debugging are also discussed. This edition has been enhanced with new material on I/Os, logic, and protocols and networking.